Prophetic leadership: Islamic psychology studies in leadership management in mobile legend games - Lalu Pradipta Jaya Bahari; Ahmad Fauzi (Yayasan Adra Karima Hubbi, 2023)
This study aims to examine the concept of prophetic leadership in the context of the Mobile Legend Game, using an Islamic psychological approach. Prophetic leadership is a leadership model derived from the exemplary behavior of the prophets and apostles in Islam. In Mobile Legend games, effective leadership is essential to achieve common goals and optimal team performance. This study used a qualitative research method with a descriptive-analytical approach. Data were collected through participatory observation, interviews, and content analysis of leader behaviors in the Mobile Legend game that demonstrate prophetic leadership characteristics. In addition, the Islamic psychology approach was used to analyze aspects of prophetic leadership, such as justice, trust, integrity, and effective communication. The results of this study are expected to provide a deeper understanding of how prophetic leadership can be applied in the context of Mobile Legend games. The implications of this study can provide insight for players and game developers in understanding the importance of leadership based on Islamic values and exploring the potential of effective leaders in games.